AUTHENTICITY OF DECLARED NOTARY ACTIVITIES BY USING THE PHOTO DOCUMENT MINUTA SIGNING OF ASSET - Putu Ayuk Sapta Agustini; I Nyoman Putu Budiartha; Ida Bagus Agung Putra Santika (Warmadewa Press, 2021)
Influence arising from technological developments has an impact on changes in society in the field of law, especially in terms of evidence using electronic devices as an extension of evidence in the law in Indonesia. This study aims to determine the responsibility of a Notary to an authentic deed made by and/or before a Notary Public based on the provisions of UUJN jo UUJN-P and to find out the legal impact arising related to the use of photo documents as an expansion of new evidence towards the authenticity of an authentic deed. The method used in this study is a normative perspective with a statutory approach and conceptual approach that aims to conduct a juridical study of the legality of electronic evidence. The results showed that the responsibility of the Notary in providing services in the field of civil law, in particular, made an authentic deed as stipulated in UUJN jo UUJN-P to provide a sense of justice for the parties, third parties with an interest in the deed he made and his heirs, were responsible for the authenticity of the deed he made it as perfect proof. In the context of the authenticity of a Notary Deed as an authentic deed, the Notary Deed does not require any other evidence to guarantee the legal certainty of its authenticity, so that the use of photo documents used as evidence in procedural law, both criminal and civil, cannot be applied or used against the Notary Deed even as evidence supporters.